A theory of tolerance - Giacomo Corneo; Olivier Jeanne (Center for Economic Studies and ifo Institute (CESifo), 2007)
We develop an economic theory of tolerance where lifestyles and traits are invested with symbolic value by people. Value systems are endogenous and taught by parents to their children. In conjunction with actual behavior, value systems determine the esteem enjoyed by individuals. Intolerant individuals attach all symbolic value to a small number of attributes and are irrespectful of people with different ones. Tolerant people have diversified values and respect social alterity. We study the formation of values attached to both endogenous and exogenous attributes, and identify circumstances under which tolerance spontaneously arises. Policy may affect the evolution of tolerance in distinctive ways, and there may be efficiency as well as equity reasons to promote tolerance.
Keywords: D1; O1; 330; value systems; tolerance; modernity; Kinder; Gesellschaftliches Bewusstsein; Risiko